Transitional entrepreneurship: Elevating research into marginalized entrepreneurs. (2nd November 2021) - Pidduck, Robert J.; Clark, Daniel R.
ABSTRACT: Socially, institutionally, culturally, or resourcefully marginalized entrepreneurial actors pursuing new ventures to achieve positional advancement hold valuable theory development potential. We refer to this emerging conceptual domain as Transitional Entrepreneurship (TE). In this thematic issue, we present seven articles united under the umbrella of TE, to introduce the domain and its conceptual boundaries. These articles, individually, study different marginalized groups but collectively provide a platform to explore TE, distinguish it from related but distinct topics, and illuminate its numerous implications for research and practice moving forward. These articles about transitional entrepreneurs differ in geography, social class, culture, race, and gender. However, the adversity faced by TEs is not unique to any one group; by considering them collectively we seek to advance knowledge about venturing in the face of social, economic, cultural, and institutional adversity.